2010
DOI: 10.1128/aem.01180-10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Bartonella Species Detected in Different Tissues of Small Mammals in Nepal

Abstract: Bartonellae were detected in a total of 152 (23.7%) of 642 tissues from 108 (48.4%) of 223 small mammals trapped in several urban areas of Nepal. Based on rpoB and gltA sequence analyses, genotypes belonging to seven known Bartonella species and five genotypes not belonging to previously known species were identified in these animals.Bartonella species are important zoonotic and vector-borne bacteria associated with an increasing array of emerging infections in humans and animals (6,8,21). Identification of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
4
28
2
Order By: Relevance
“…However, most GenBank data for Bartonella includes only gltA sequences (i.e., no 16S rDNA). We therefore employed a network approach to explore a more extensive data set, combining GenBank data (Concannon et al, 2005;Abbot et al, 2007;Harrus et al, 2009;Kosoy et al, 2009Kosoy et al, , 2010Bai et al, 2010Bai et al, , 2011Gundi et al, 2010;Billeter et al, 2012) with sequences generated in this effort [Tables 1 and S1]. The advantage of a network approach is that it avoids representation of strict binary sequence relationships, and rather presents simultaneous alternative connections.…”
Section: Network Analysismentioning
confidence: 99%
“…However, most GenBank data for Bartonella includes only gltA sequences (i.e., no 16S rDNA). We therefore employed a network approach to explore a more extensive data set, combining GenBank data (Concannon et al, 2005;Abbot et al, 2007;Harrus et al, 2009;Kosoy et al, 2009Kosoy et al, , 2010Bai et al, 2010Bai et al, , 2011Gundi et al, 2010;Billeter et al, 2012) with sequences generated in this effort [Tables 1 and S1]. The advantage of a network approach is that it avoids representation of strict binary sequence relationships, and rather presents simultaneous alternative connections.…”
Section: Network Analysismentioning
confidence: 99%
“…Only one study focused on detecting and genotyping Bartonella DNA in cat blood found the ITS and gltA targets to be equally productive (Bai et al 2015b). While detecting and genotyping Bartonella in rodent spleens, two studies reported successful identification in more specimens by targeting the rpoB gene compared with the gltA (Gundi et al 2010(Gundi et al , 2012b). …”
Section: Comparison Of Genetic Markers For Detection and Genotyping Omentioning
confidence: 99%
“…4,5 The occurrence of bartonellae in rodents and other small mammals has been reported in several countries in Asia, including Bangladesh, China, Indonesia, Japan, Laos, Cambodia, Taiwan, Nepal, and Thailand. [6][7][8][9][10][11][12][13][14][15][16][17] Bartonella tribocorum, B. rattimassiliensis, B. coopersplainsensis, B. elizabethae, and B. queenslandensis are among those that have been identified from the wild rats (Rattus species). Arthropod vectors, particularly fleas (Ctenocephalides felis) and ticks (Ixodes, Haemaphysalis), are often implicated in the natural maintenance of various species of bartonellae.…”
mentioning
confidence: 99%